Representative meteorological data for long-term wind-driven rain obtained from Latin Hypercube Sampling – Application to impact analysis of climate change. (15th January 2023) - Bourcet, J.; Kubilay, A.; Derome, D.; Carmeliet, J.
Abstract: Accurate estimation of wind-driven rain (WDR) load on building facades is of paramount importance for the assessment of moisture-induced damage risks. The response of the facade depends on the used meteorological data, which can show significant variation over time, especially considering climate change. In this study, a statistical approach based on a Latin Hypercube Sampling (LHS) is used to generate reduced samples, which accurately represent long-term meteorological conditions for WDR. Based on cumulative distribution functions, the generated samples with LHS are a subset of actual measured data, independent of the temporal information, and are clustered around values of highest frequency. Computational fluid dynamics (CFD) simulations of WDR are performed on a historical building located in Victoria, BC, Canada based on a previously validated methodology, determining the parts of facade receiving the highest WDR load. The sensitivity study shows that a sample size of 200 with LHS, corresponding to around 0.2% of the total measured data and 4.1% of the data during rainfall, is sufficient to replicate successfully the spatial distribution of WDR with a maximum discrepancy of 7%. The reduced samples can be easily modified to model various scenarios with respect to the climate change. The change in WDR load is presented for different scenarios in terms of rainfall intensity and wind speed as predicted by future climatic conditions. The results indicate that the future WDR load depends highly on the wind speed conditions, even when wind speed is kept constant and only rainfall intensity is varied. Highlights: Long-term representative data are generated with Latin Hypercube Sampling. The generated reduced samples successfully replicate wind-driven rain load. 4% of measured rain data is enough to replicate wind rose and driving-rain index. Largest impact on future wind-driven rain load is when the wind velocity changes. Change in catch ratio at increased future rainfall intensity depends on wind speed.